Advances in RIPK1 kinase inhibitors - Chen, Lu; Zhang, Xiaoqin; Ou, Yaqing; Liu, Maoyu; Yu, Dongke; Song, Zhiheng; Niu, Lihong; Zhang, Lijuan; Shi, Jianyou (Frontiers in Pharmacology, 2022)
Programmed necrosis is a new modulated cell death mode with necrotizing morphological characteristics. Receptor-interacting protein 1 (RIP1) is a critical mediator of the programmed necrosis pathway that is involved in stroke, myocardial infarction, fatal systemic inflammatory response syndrome, Alzheimer's disease, and malignancy. At present, the reported inhibitors are divided into four categories. the first category is the type I ATP-competitive kinase inhibitors that targets the area occupied by the ATP adenylate ring; The second category is type Ⅱ ATP competitive kinase inhibitors targeting the DLG-out conformation of RIP1; The third category is type Ⅲ kinase inhibitors that compete for binding to allosteric sites near ATP pockets; The last category is other. This paper reviews the structure, biological function, and recent research progress of receptor interaction protein-1 kinase inhibitors.